2022
DOI: 10.1158/2326-6066.cir-21-0722
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization and Phase I Study of an Anti–HER2-TLR7 Immune-Stimulator Antibody Conjugate in Patients with HER2+ Malignancies

Abstract: Immune-stimulator antibody conjugates (ISACs) combining tumor-targeting monoclonal antibodies with immunostimulatory agents allow targeted delivery of immune activators into tumors. NJH395 is a novel, first-in-class ISAC comprising a toll-like receptor 7 (TLR7) agonist conjugated to an anti-HER2 via a non-cleavable linker-payload. Preclinical characterization showed ISAC-mediated activation of myeloid cells in the presence of antigen-expressing cancer cells, with antigen targeting and TLR7 agonism contributing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Since the intensity of TCR stimulation on CTLs has been reported to be critical in inducing differentiation of memory T cells ( 54 ), it is conceivable that the combination of DSP-0509 with anti-CTLA-4 antibody increased the antigen-presenting ability of DCs, resulting in increased TCR signal on CTL. Recent approach in TLR7 agonist drug discovery is focusing on tumor targeting modality including ADC and nanoparticle and so on ( 55 58 ). However, these approaches are not always succeeded so far.…”
Section: Discussionmentioning
confidence: 99%
“…Since the intensity of TCR stimulation on CTLs has been reported to be critical in inducing differentiation of memory T cells ( 54 ), it is conceivable that the combination of DSP-0509 with anti-CTLA-4 antibody increased the antigen-presenting ability of DCs, resulting in increased TCR signal on CTL. Recent approach in TLR7 agonist drug discovery is focusing on tumor targeting modality including ADC and nanoparticle and so on ( 55 58 ). However, these approaches are not always succeeded so far.…”
Section: Discussionmentioning
confidence: 99%
“…Data from 18 patients enrolled in the single ascending dose escalation (part I) demonstrated that NJH395 could efficiently deliver the TLR7 agonist moiety in HER2 + cancer cells. 25 , 26 Additionally, NJH395 induced IFN-I responses, which correlated with immune modulation in the tumor microenvironment. 25 , 26 Although cytokine release syndrome was common, it remained manageable.…”
Section: Introductionmentioning
confidence: 86%
“… 25 , 26 Additionally, NJH395 induced IFN-I responses, which correlated with immune modulation in the tumor microenvironment. 25 , 26 Although cytokine release syndrome was common, it remained manageable. On the other hand, antidrug antibodies and neuroinflammation at high doses represent significant clinical challenges.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Intravenous NJH395 is an immune-stimulating antibody conjugate (ISAC) that combines an unspecified TLR7 agonist with a monoclonal antibody against human epidermal growth factor receptor-2 (HER2) 40 . Despite its systemic distribution, the HER2 component directs the TLR7 agonist specifically to HER2expressing cells, enabling it to act locally and theoretically limit its off-target effects.…”
Section: Agonists Of Intracellular Tlrsmentioning
confidence: 99%